Pension Incentives and Labor Supply: Evidence from the Introduction of Universal Old-Age Assistance in the UK - Matthias Giesecke; Philipp Jaeger (Institute of Labor Economics (IZA), 2021)
We study the labor supply implications of the Old-Age Pension Act (OPA) of 1908, which, for the first time, provided pensions to older people in the UK. Using recently released census data covering the entire population, we exploit variation at the newly created age-based eligibility threshold. Our results show a considerable and abrupt decline in labor force participation of 6.0 percentage points (13%) when older workers reach the eligibility age of 70. To mitigate the impact of population aging today, pension reforms aimed at increasing elderly labor supply, however, have to induce much larger behavioral responses than the OPA.
Keywords: D61; H21; H55; J14; J22; J26; 330; old-age assistance; labor supply; retirement; regression discontinuity design; equity-efficiency trade-off